Trends in Outside Support for Insurgent Movements - Byman, Daniel; Chalk, Peter; Hoffman, Bruce; Rosenau, William; Brannan, David (RAND Corporation, 2023)
The most useful forms of outside support for an insurgent movement include safe havens, financial support, political backing, and direct military assistance. Because states are able to provide all of these types of assistance, their support has had a profound impact on the effectiveness of many rebel movements since the end of the Cold War. However, state support is no longer the only, or indeed necessarily the most important, game in town. Diasporas have played a particularly important role in sustaining several strong insurgencies. More rarely, refugees, guerrilla groups, or other types of non-state supporters play a significant role in creating or sustaining an insurgency, offering fighters, training, or other forms of assistance. This report assesses post-Cold War trends in external support for insurgent movements. It describes the frequency that states, diasporas, refugees, and other non-state actors back guerrilla movements. It also assesses the motivations of these actors and which types of support matter most. This book concludes by assessing the implications for analysts of insurgent movements.